1996
DOI: 10.1021/jp9524340
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Hybrid Density Functional/Hartree−Fock Approaches for the Study of Homogeneous Catalysis

Abstract: The potentialities of a hybrid density functional/Hartree-Fock approach in the study of homogeneous catalysis have been investigated by a comprehensive study of binary adducts of copper atom characterized by strong (Cu 2 , CuH, CuCH 3 ) or weak (CuCO, CuNO, CuO 2 , CuC 2 H 2 ) metal-ligand interactions. The results confirm that this approach describes with good accuracy several properties of transition metal complexes, giving in particular binding energies close to the best available post-Hartree-Fock and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 84 publications
4
32
0
Order By: Relevance
“…However, the order of isomers as the structures A, C, and B in increasing energy observed in earlier DFT works is now altered in the present work due to the new isomer (D) found in this work. This isomer is the next low-lying isomer to the lowest energy [14,21,23]. The lowest-energy structure has a doublet state in agreement with the experimental observation [12,16].…”
Section: B Cuo2supporting
confidence: 82%
See 1 more Smart Citation
“…However, the order of isomers as the structures A, C, and B in increasing energy observed in earlier DFT works is now altered in the present work due to the new isomer (D) found in this work. This isomer is the next low-lying isomer to the lowest energy [14,21,23]. The lowest-energy structure has a doublet state in agreement with the experimental observation [12,16].…”
Section: B Cuo2supporting
confidence: 82%
“…Our vibrational frequency calculations have shown that the side on C isomer has one imaginary frequency. Such imaginary frequency for this isomer has also been observed in the earlier density functional based work of Barone and Adamo [14]. Earlier quantum chemical calculation by Bauschlicher [23] found isomer C to be more stable than the bent structure A.…”
Section: B Cuo2supporting
confidence: 79%
“…DFT calculations are discussed first. The Kohn ± Sham formulation of density functional theory provides geometric data for transition metal complexes (amongst others) that are comparable with highly correlated Hartree ± Fock calculations [19] and leads to molecular orbitals with a good physical basis; [20] thus we have confidence in using these in our analyses.…”
Section: Evidence From Crystallographymentioning
confidence: 99%
“…A hybrid method consisting of HF and DFT, known as the self-consistent hybrid (SCH) approach or B3LYP [16,17] approach is used. The B3LYP method can provide reliable geometric, thermodynamic and spectroscopic parameters for metal-ligand interactions, ranging from covalent bonds to weak non-covalent interactions [18][19][20]. It is the combination of HF and Becke exchange [21] with the Lee-Yang-Parr (LYP) correlation potential [22].…”
Section: Density Functional Theorymentioning
confidence: 99%